Analysis of Oil Distribution and Reduction of Axial Force due to Oil Supply in a Multi-Plate Clutch - Groetsch, Daniel; Motzet, Rudi; Voelkel, Katharina; Pflaum, Hermann; Stahl, Karsten (Tribology in Industry, 2022)
Wet multi-plate clutches enable safety-critical operations in various types of powertrains. Ensuring sufficient oil coverage on each friction interface of industrial clutches is achieved by pressurized oil supply. The challenge of building capable test rigs to study oil and pressure distribution inside a practically relevant loaded clutch and the limited availability of test parts due to small batch sizes determine the demand for numerical studies. This contribution presents results obtained by experimentation on a component test rig and by numerical studies with computational fluid mechanics of a wet industrial clutch. A transient moving mesh approach with a laminar, incompressible, and isothermal flow model is applied to the fluid domain representing the test rig setup. The investigations are validated by comparing pressure measurements with simulation results. The influences of varying operating conditions (oil flow, speed) and geometry of oil supply in the inner carrier on the oil and pressure distributions are analyzed. Regardless of operating conditions or geometrical variations of the inner carrier, a nearly uniform oil supply to all friction interfaces is achieved. The hydraulic oil pressure lowers the effective axial force at the friction interfaces, and therefore reduces torque transfer capacity up to 29%, depending on operating conditions.
CRIS-Team Scopus Importer:2025-05-19
Keywords: Clutch simulation; Computational fluid dynamics (CFD); Constant slip; Limited slip; Oil distribution; Oil distributor design; Oil supply design; Pressurized oil supply; Reduced pressure; Sealed clutch; Wet clutch